QUALITY OF INDOOR AIR IN SMALL CZECH FURNITURE COMPANIES - Tesařová, Daniela; Čech, Petr (Innovation in Woodworking Industry and Engineering design, 2013)
This paper investigates the problematic of emission volatile organic compounds emitted to working, indoor air of the wooden furniture company. The main goal of this research were assessment of quality of indoor air in working environment, which was load of emission VOC emitted from production processes of made furniture. The one part of this research deals of the influence individual technological operations in wooden made furniture in dependence on quality and quantity composition of VOC, which they effects of quality external and internal environment of the furniture company. We analyzed emissions of VOC emitted during the furniture production by the gas chromatograph in conjunction with mass spectrometer and Direct Thermal Desorption. The result of analysis is qualitative and quantitative data in form graph and numerical expression.